Some helminth parasites of marine fishes of South Africa: Families Gorgoderidae, Zoogonidae, Cephaloporidae, Acanthocolpidae and Lepocreadiidae (Digenea) - Bray, R. A. (Journal of Natural History, 1985)
The following digeneans are described, recorded or figured from South African waters: Phyllodistomum tongaatense sp. nov. from Coracinus multifasciatus; Steganodermatoides [= Proctophantastes] allocytti comb. nov. (syn. Hudsonia pacifica) from Neocyttus rhomboidalis; Overstreetia sodwanaensis gen. et. sp. nov. from Pranesus pinguis; Cephaloporus bakeri sp. nov. from Pervagor melanocephala; Stephanostomum (?) solontschenki from Merluccius capensis; S. ditrematis from Megalaspis cordyla; Stephanostomum. spp. metacercariae from Merluccius capensis and Chaetodon marleyi; Lepidapedon (Lepidapedoides) nicolli from Epinephelus albomarginatus; Holorchis pycnoporus (syns: legendrei, ioannoui) from Sparodon durbanensis and Diplodus sargus; Pseudaephnidiogenes rhabdosargi from Rhabdosargus sarba and R. holubi; P. rossi sp. nov. from Caffrogobius nudiceps; Clavogalea gaevskayae gen. et sp. nov. from Trachinotus botla. The following other taxa are discussed: genus Steganodermatoides (syns: Hudsonia, Allosteganoderma); family Cephaloporidae; genus Stephanostomum; subgenus Lepidapedon) (Lepidapedoides); subfamily Aephnidiogeninae and subfamily Acanthogaleinae.